RANCANG BANGUN ANTENA MIKROSTRIP ARRAY 4X1 PATCH SQUARE UNTUK JARINGAN WIFI - Aprinal Adila Asril (Jurnal Ilmiah Poli Rekayasa, 2026)
This research aims to design and implement a  microstrip array 4x1 patch square antenna for a WiFi using the software CST Studio Suite 2019and using a Vector Network Analyzer for antenna testing. Some antenna parameters that were determined include return loss, bandwidth, VSWR, radial pattern, and gain. This antenna has an antenna size of 125 x 130 mm. The antenna isdesigned based on the characteristics of several antenna parameters, namelyhaving a return loss of ≤-10 dB, a gain value of ≥1 dB, and a VSWR ≤2. The type of substrate used is FR-4 (lossy) with a dielectric constant specification of 4.3, characteristic impedance of 50 ohms and thickness of 1.6 mm. The groundplane material used is copper with a thickness of 0.035 mm. The results of optimizing the microstrip array antenna parameters are a return loss of -17.72 dB with a frequency of 2.4 GHz, a VSWR value of 1.34 with a frequency of 2.4 GHz and has a unidirectional radiation pattern. Meanwhile, the return loss value for the manufactured antenna was found to be -18.7 dB with a frequency of 2.46 GHz and a VSWR value of 1.26 with a frequency of 2.46 GHz.   Keywords: Antena Mikrostrip Array,  Return loss, bandwidth, VSWR, Pola radiasi, dan gain.